Purchase Decision (Study At: Delia Hijab Sukabumi) - Nashr, Muhammad Raka Pawitra Abdul; Irawan, Herry (eProceedings of Management, 2023)
Business competition at this time, calls all companies to reply and meet customer wishes by using continuing tocreate new innovations. businesses should layout a marketing strategy, particularly STP (segmentation,concentrated on and positioning) that is accurate to win marketplace competition. This study aims to determinethe effect of STP on purchasing decisions. The method of analysis of this research is quantitative. The populationof this study were Delia Hijab consumers who were also used as a sample which was taken as many as 100. Thesampling technique was simple convenience. The results of this study indicate that Segmentation, Targeting, andPositioning simultaneously have a significant effect on purchasing decisions. Segmentation partially has apositive and significant influence on purchasing decisions. Targeting partially positive and significant influenceon purchasing decisions. Positioning is partially positive and significant influence on purchasing decisions.Delia Hijab is one of the well-known shops in the city of Sukabumi, for the future it must have a better image sothat consumers will feel more satisfied with the products offered and will make consumers buy long-termproducts.Keywords-Segmenting, Targeting, Positioning, Purchase Decision